Intracerebral Hemorrhage: A Rare Snake Bite Sequelae - Jalal, Muhammed Jasim Abdul; Thomas, Annie; Varghese, Prithvi (Indian Journal of Neurosurgery, 2017)
Introduction Annually, more than 2,500,000 snake bites are reported in India, out of which 30,000 to 50,000 cases end in mortality. Here, we report an unusual complication of intracerebral hemorrhage following a snake bite.Case Report A 48-year-old diabetic and hypertensive male patient presented with loss of consciousness following a suspected snake bite. Unconsciousness was preceded by vomiting. His neurological status deteriorated to a Glasgow coma score of 7/15 (E1M5V1). Pupils showed anisocoria. Computed tomographic scan of the brain revealed large intracerebral hemorrhage in the left temporal lobe and another large intracerebral hemorrhage in the left parietal lobe with significant mass effect and signs of early transtentorial herniation. He was taken up for left frontotemporoparietal craniotomy and evacuation of left temporoparietal intracerebral hemorrhage.Conclusion Cerebral complications following snake bite envenomation include infarcts and hemorrhages. Even though rare in incidence, cerebral complications following snake bites are associated with high morbidity and mortality. The patient presented here had left temporal and left parietal intraparenchymal hemorrhage with impending transtentorial herniation following a snake bite. Prompt treatment of raised intracranial tension simultaneously with aggressive correction of the coagulation disorders and appropriate supportive measures can result in better outcomes in patients having cerebral complications of snake bite envenomation.
Keywords: snake bite; intracerebral hemorrhage; coagulopathy